Loss-of-function polymorphisms in the organic cation transporter OCT1 are associated with reduced postoperative tramadol consumption. Issue 11 (November 2016) - Stamer, Ulrike M.; Musshoff, Frank; Stüber, Frank; Brockmöller, Jürgen; Steffens, Michael; Tzvetkov, Mladen V.
Abstract : Abstract: The organic cation transporter OCT1 (SLC22A1) mediates uptake and metabolism of the active tramadol metabolite (+) O -desmethyltramadol in the liver. In this study, the influence of OCT1 genetic polymorphisms on pharmacokinetics and analgesic efficacy of tramadol in patients recovering from surgery was analyzed in addition to the CYP2D6 genotype. Postoperative patients who received tramadol through patient-controlled analgesia were enrolled. Genotypes resulting in 0, 1, or 2 active OCT1 alleles were determined as well as CYP2D6 genotypes. The primary endpoint was the 24-hour postoperative tramadol consumption in patients with 0 vs at least 1 active OCT1 allele. Secondary endpoint was the OCT1-dependent plasma concentration (areas under the concentration–time curves) of the active tramadol metabolite (+) O -desmethyltramadol. Of 205 patients, 19, 82, and 104 carried 0, 1, and 2 active OCT1 alleles, respectively. Cumulative tramadol consumption through patient-controlled analgesia was lowest in patients with 0 active OCT1 allele compared with the group of patients with 1 or 2 active alleles (343 ± 235 vs 484 ± 276 mg; P = 0.03). Multiple regression revealed that the number of active OCT1 alleles ( P = 0.014), CYP2D6 ( P = 0.001), pain scores ( P < 0.001), and the extent of surgery (0.034) had a significant influence on tramadol consumption. Plasma areas under the concentration–time curves of (+) O -desmethyltramadol were 111.8 (95% confidence interval: 63.4-160.1), 80.2 (65.1-95.3), and 64.5 (51.9-77.2) h·ng·mL −1 in carriers of 0, 1, or 2 active OCT1 alleles ( P = 0.03). Loss of OCT1 function resulted in reduced tramadol consumption and increased plasma concentrations of (+) O -desmethyltramadol in patients recovering from surgery. Therefore, analyzing OCT1 next to CYP2D6 genotype might further improve future genotype-dependent dose recommendations for tramadol. Abstract : In patients receiving tramadol for postoperative analgesia, genetic variants of CYP2D6 and OCT1 influenced tramadol consumption and plasma concentrations of (+) O -desmethyltramadol.